Magenkrebs: Krankheits- und behandlungsbedingte Belastungen von Patienten und Erfordernisse an die Unterstützung durch ihre Ärzte = Gastric cancer : disease and treatment-related problems of patients and demands on support by physicians - Keller, Monika (Der Onkologe, 2016)
Physical symptoms and functional impairment related both to disease and cancer treatment are common among gastric cancer patients with weight loss, nutritional problems, pain and fatigue prevailing. Impaired functioning and physical problems can adversely affect the quality of life (QoL). Mental health problems, such as anxiety, worries, depressed mood and disturbed sleep, however, do not exceed that of other cancer patients. During the first months following total or subtotal gastrectomy, patients experience impaired physical health and compromised quality of life while mental health often continuously improves soon after successful surgery. Living without a stomach while maintaining quality of life requires a lengthy and profound adjustment process. This process is best supported by timely, continuous education and counseling from physicians. Close monitoring of health and nutritional status is recommended to ensure early detection and treatment of malnutrition and other complications arising from gastrectomy. Psychological problems and disorders frequently arise with critical events, e. g. progressive disease, functional impairment and perceived loss of control. Continued support from physicians is effective in promoting patient adjustment to cancer and can therefore prevent crises. Close monitoring of a patient’s physical and mental health during the course of illness, at all critical key points allows timely detection of emotional and social problems, thereby preventing crises. Psychological distress and crisis reactions can be effectively ameliorated through supportive psychological interventions complemented by psychopharmacological treatment. This is best achieved by close collaboration between physicians and mental health professionals.